Decreased Growth with Serotonin Reuptake Inhibitors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Growth and growth hormone secretion were evaluated in 4 children (3 boys), aged 11.6 to 13.7 years, treated with selective serotonin reuptake inhibitors (SSRIs) for obsessive compulsive disorder or Tourette syndrome, at Schneider Children's Medical Center of Israel, Petah Tikva, and Sackler School of Medicine, Tel Aviv University, Tel Aviv.